A reflexão crítica na formação contínua de professores de inglês da escola pública - Araújo, Jeferson Cipriano de (2019)
This research aims at critically understand senses and meanings atributed by teacher educators to critical reflective education, which occurs in a specialization course designed to teachers from state and municipal schools of São Paulo and how these senses and meanings expressed can reveal about their practice. The researcher and three teacher educators from the specialization course were part of this research, being interviewed through semi structured questions (LÜDKE & ANDRÉ,1986; NININ, 2018) by social media. This research is inserted in the Critical Applied Linguistics field (MOITA LOPES, 2006; PENNYCOOK, 2006) and in the theoretical and methodological Critical Paradigm (KINCHELOE & McLAREN 2006; LINCOLN & GUBA, 2006; GARCIA, 2003). It was based on Cultural-Historical Theory (VYGOTSKY, 2000, 1991; MORAES, 2008; BLANCK, 1996), taking into account concepts as mediation, senses and meanings as well as Zone of Proximal Development (DANIELS, 2003, 2008; VYGOTSKY, 2000, 2001, 2010). Also, it discussed pedagogical practice in the light of critical reflective practice, based on the (multi)referenciality of classical and contemporary scholars (SCHÖN, 1992, 2000; PÉREZ GÓMEZ, 1992; FREIRE, 1979, 1983, 1996, 1997, 2001; NÓVOA, 2006; SMYTH, 1992; FRANCO, 2015, 2016). The data were analized from socio-discursive interactionism by thematic content clippings and from them it was possible to develop a critical analysis on the theoretical approach. The results confirmed the senses and meanings on responsibility and reflected actions, being essential for the exercise of teaching in the role of a teacher trainer in a specialization course which aims at public schools' teachers reflective practice. It expressed the view of teacher trainers on in-service teachers on how they deconstruct their own teaching practice on self-knowledge about critical reflective practice. This discussion has been relevant, since it considers learning-teaching, from a cultural-historical perspective, as a mutual, continuing and confronting process, in which professional identity is always being reconstructed, likely to change the teaching practice in the teacher's practice educator, being directly focused on pedagogical practice in the public schools' professionals